Tobacco Smoking and Association between Betel Nut Chewing and Metabolic Abnormalities Among Military Males: The CHIEF Study - Lin, Yen-Po; Tsai, Kun-Zhe; Chang, Chih-Yu; Su, Fang-Ying; Han, Chih-Lu; Lin, Gen-Min (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2021)
Aim: To investigate the effect of smoking and alcohol intake on the association between betel nut chewing and each metabolic abnormality. Background: Betel nut chewing has been associated with metabolic syndrome. Objective: Whether the association is affected by tobacco or alcohol use is not clarified so far. Methods: The authors conducted a cross-sectional study using 6,657 military males, aged 18-50 years in eastern Taiwan in 2013-2014. Metabolic syndrome was defined according to the International Diabetes Federation’s ethnic criteria for Asians. The population was classified as non-betel nut chewers (N =5,749), current chewers with both tobacco and alcohol use (N =615), and current chewers without tobacco and/or alcohol use (N =293). Multiple logistic regression analyses were stepwise adjusted for the confounders including alcohol and tobacco use to determine the association of betel chewing with the metabolic abnormalities. Results: As compared to the non-current chewers, the current chewers with both tobacco/alcohol use and those without had a higher risk of metabolic syndrome (odds ratios (OR) and 95% confidence intervals: 2.46 (2.00-3.02), and 2.04 (1.53-2.73), respectively) after controlling for age, service specialty, total cholesterol levels ≥200 mg/dL and exercise frequency (model 1). The association did not change much in the two chewing groups after additionally adjusting for alcohol consumption (model 2) (OR: 2.49 (1.99-3.12), and 2.04 (1.52-2.73), respectively), whereas the relationship reduced significantly in the chewers with both tobacco/alcohol use rather than those without after further adjusting for smoking (model 3) (OR: 2.18 (1.71-2.78) and 2.02 (1.51-2.71), respectively). This was in parallel with the pattern for the association of betel nut chewing with serum triglycerides >150 mg/dL in the chewers with both tobacco/alcohol use and those without in model 1 (OR: 2.90 (2.40-3.51) and 1.90 (1.45-2.49), respectively, p =0.011), in model 2 (OR: 2.82 (2.30-3.46) and 1.89 (1.44-2.49), respectively, p =0.040), and in model 3 (2.26 (1.81-2.81) and 1.87 (1.42-2.45), respectively, p =0.76). Conclusion: Our findings suggest that tobacco smoking but not alcohol intake could increase the relationship of betel nut chewing with metabolic syndrome, which is likely mediated by a synergic effect on increasing serum triglycerides levels.
Keywords: metabolic syndrome